Job Stress and Risk Management Related to Environmental Pollution Resulting from Electricy Generation Station in Musayyib/Iraq - Kadhim Abbas, Sahar (International Journal of Psychosocial Rehabilitation, 2020)
Background: Environmental pollution has become an issue of concern to all countries of the world after its high rates of proliferation, which coincide with the degree of technological and industrial development. The study aims to assess the job stress and risk management concerning environmental pollution and also to determine the relationship between job stress and risk management. Methodology: A descriptive correlational study is carried out in the north Babylon Governorate, as in Musayyib City. By a non-probability "convenience" account, 100 subjects are selected for the purpose of the present study. A questionnaire as a means for data collection consists of demographic data and risk management and job stress. By self-administration, data are collected from those who work in the electrical generation plant and analyzed through the use of descriptive and inferential approaches. Results: Findings reveal that 55% are within the first age group (25-35 years old), 78% are male, 36% are preparatory educated, 77% do administrative work and accounting, and 33% of workers are training in one course. Seventy percent were not available for risk management, and fifty percent always had job stress. As well as, the job stress has been influenced by the management at a p-value of > 0.01. Conclusion: The psychological aspect is a very important factor in the administrative aspects; the more psychological stress factors, the lower the performance of his work. Decision-makers need to provide the necessary health facilities to staff because of minimizing the negative effects. Also, you must conduct further studies to determine the causes of work stress.